Esensi Wali Nikah Perspektif Surat An-Nisa dan Relevansinya Terhadap Masyarakat Modern - Afdilla Nisa; Andriyaldi Andriyaldi (USRATY : Journal of Islamic Family Law, 2023)
This article explores the essence of marriage guardian in the perspective of Surah An-Nisa in the Koran and its relevance in modern society. Surat An-Nisa discusses the laws of marriage and women's rights, including the role of marriage guardian. This study analyzes verses related to marriage guardians and the interpretations of prominent scholars. The results show that the essence of marriage guardians, such as protecting women's rights and giving consent in good faith and being a mediator in resolving conflicts, remains relevant in maintaining a just marriage institution. However, challenges arise in the context of an increasingly inclusive and complex modern society. A solution is needed to integrate Islamic values that respect gender equality with tradition and modernity. An in-depth understanding of the essence of marriage guardians from the perspective of the Koran is important to support healthy and harmonious marriage relations in this era of globalization.